'No one here's helping me, what do you do?': addressing patient need for support and advice about stem cell treatments. (October 2017) - Tanner, Claire; Petersen, Alan; Munsie, Megan
Aim: This article examines how those who contemplate purported stem cell treatments (SCTs) negotiate available information sources and the adequacy of current approaches to guidance and support.Materials & methods: Qualitative interviews undertaken with people who had contemplated or undergone purported SCTs for a range of conditions (n = 24 and n = 27, respectively), as well as professionals who are frequently asked about SCTs (n = 20) were analyzed.Results: Our findings reveal the difficulties for individuals in discriminating between different sources of information on SCTs and the limitations of current responses.Conclusion: In the context of contending information about SCTs informal ('accidental') advisors potentially play a crucial role in supporting patients. Additional approaches are also required to better address patients' needs.